Guerilla Tv i wideo art jako narzędzia w walce z telewizyjnym establishmentem Stanów Zjednoczonych - GIEC, MARTA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Guerilla Tv and video art as a tool in the fi ght against the television establishment in USA An article is based on the issue of the main mediated model of one-way communication connected with the mass media and looks at the problem of television networks in USA in the 1960s and 70s, which was highly influential. This political and cultural situation had been developing out of techni- cal innovations and become a point of departure for considering alternative video communication, which stood up against the institutionalized television regime. At this time, video art and especially Guerilla Tv were the bearers of the new communication order, at the same time breaking the imposed socio-political discourse.